Functional analysis - Rao, K. Chandrasekhara (Alpha Science International, 2006)
Complied from class-tested lecture notes, this text focuses on various aspects of Banach spaces, Hilbert spaces, operator theory, Banach algebras and topological vector spaces. The author includes several solved problems and exercises at the end of each chapter. Complete and detailed proofs of all theorems and applications are also included.